2007
DOI: 10.1111/j.1467-9906.2007.00344.x
|View full text |Cite
|
Sign up to set email alerts
|

Involuntary Isolation: Ethnic Preferences and Residential Segregation

Abstract: In recent years, there has been a substantial amount of empirical work done on the causes of residential segregation. Nevertheless, better understanding of to what extent ethnic groups choose to live in the proximity of each other, or to what extent segregation is forced upon them is imperative. Prior research on self-segregation either focused on discovering underlying motivations for self-segregation, or the effect of stated preferences on observed patterns of segregation, whereas few studies directly link m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 28 publications
2
27
0
1
Order By: Relevance
“…Finally, the 'ethnic enclave' model is centred on the individual preference of minority ethnic households. In this perspective, the preference of ethnic groups to live in concentrated neighbourhoods is seen as the major force in producing segregation (Clark, 1991;van der Laan Bouma-Doff, 2007). Bolt et al (2008) found that self-segregation tendencies are relatively stronger among the native majority, so research on ethnic specificity in neighbourhood preferences should not focus only on ethnic minorities.…”
Section: Ethnic Differences In Locational Choicementioning
confidence: 98%
“…Finally, the 'ethnic enclave' model is centred on the individual preference of minority ethnic households. In this perspective, the preference of ethnic groups to live in concentrated neighbourhoods is seen as the major force in producing segregation (Clark, 1991;van der Laan Bouma-Doff, 2007). Bolt et al (2008) found that self-segregation tendencies are relatively stronger among the native majority, so research on ethnic specificity in neighbourhood preferences should not focus only on ethnic minorities.…”
Section: Ethnic Differences In Locational Choicementioning
confidence: 98%
“…It has been an ongoing debate among European researchers to what degree they are valid in European contexts due to the differences in social welfare and housing systems that reduce differences between neighborhoods (Friedrichs et al, 2003; Kesteloot, Murie, & Musterd, 2006). These doubts might be most applicable to the case of the Netherlands, where levels of income and ethnic segregation have been traditionally low (Laan Bouma‐Doff, 2007; Musterd, 2003) as result of a large supply of affordable social housing in major cities, extensive welfare programs of the national government, and active state involvement at the local level. In recent years, it has nevertheless been shown through a number of quantitative studies that these factors do not entirely compensate or mute neighborhood effects on employment and social mobility (Klaauw & Ours, 2003; Musterd et al, 2003).…”
Section: The Dutch Contextmentioning
confidence: 99%
“…Indeed, in some contexts and for some ethnic communities, segregation can be largely due to preferences (e.g. whites in the USA and natives in Europe as shown by Charles [2000] and van der Laan Bouma- Doff [2007]), while for other ethnicities, especially those who exhibit a weaker socioeconomic position, choices can be significantly constrained. Nevertheless, the literature has shown how puzzling it is to identify and untangle the real causes driving segregation phenomena, in part due to the opposite effects they may have.…”
Section: The Debate Over Voluntary and Involuntary Causes Of Ethnic Smentioning
confidence: 99%
“…In the case of residential markets, we cannot use revealed preferences due to the choice-constraint issue (see. Van der Laan Bouma Doff, 2007), which is related to the socioeconomic position of ethnic minorities and thus price, discrimination and other causes of accessibility constraints which do not allow a free choice among neighbourhoods especially for disadvantaged ethnic communities. These correlations would prevent us from producing meaningful estimates of the relative importance of different neighbourhood characteristics.…”
Section: The Stated Preference Experiments Of Neighbourhood Choicementioning
confidence: 99%
See 1 more Smart Citation